Evaluation of serum and cerebrospinal fluid biomarkers after vaccination against SARS‐CoV‐2 - Salvatore Iacono; Tommaso Piccoli; Paolo Aridon; Giuseppe Schirò; Valeria Blandino; Domenico Tarantino; Luisa Agnello; Marcello Ciaccio; Paolo Ragonese; Giuseppe Salemi (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective Vaccines are a major achievement of science, and new vaccines against SARS‐CoV‐2 are protecting the entire population from a life‐threatening infection. Although several neurological complications or worsening of pre‐existing neurological conditions after vaccination have been observed, whether a biological plausibility exist between new vaccines against‐SARS‐CoV‐2 and neurological consequences is unclear. The aim of this study is to evaluate whether vaccines against SARS‐CoV‐2 induce systemic or cerebrospinal fluid alterations in patients with neurological disorders. Methods Patients who underwent lumbar puncture (LP) between February 2021 and October 2022 were enrolled. Serum C‐reactive protein (CRP), neutrophil to lymphocyte ratio (NLR), cerebrospinal fluid total protein content (CSF‐TPc), glucose CSF/serum ratio, number of CSF cells per cubic millimeter, and CSF neurofilament light chain (CSF‐NfL) were compared between unvaccinated and vaccinated patients. Results A total of 110 patients were included and fitted into three groups according firstly to vaccination status (vaccinated and unvaccinated) and then to time from last dose of vaccine to LP (within or after 3 months). TPc, CSF/SGlu ratio, number of cells per cubic millimeter, CSF‐NfL, CRP, and NLR were not different between groups (all p > 0.05), and also, they did not differ neither according to age nor diagnosis. No relevant differences between groups were also noticed when the at‐risk time window was set to 6 weeks. Interpretation No signs of neuroinflammation, axonal loss and systemic inflammation were found in patients with neurological disorders after anti‐SARS‐CoV‐2 vaccination compared with unvaccinated ones.